The New Paradigm for Learning: The Role of the Library and Information Technologies as a Base for Life-Long Learning Skills - Lasić-Lazić, Jadranka (2000)
The paper will summarise both existing and potential functions the library will provide in the information society. Traditional and modern information skills will be considered along with the impact they have in a technologically changed environment. The paper will try to explain the impact a modern library could have on the information society (and vice versa). Special emphasis is placed on the role the library has in developing users' information skills, and on being an environment for lifelong learning.
Projekt MZOS
ENG